Functional Properties of Shape Memory Bimetal Plate. (2015) - Belyaev, S.; Evard, M.; Lomakin, I.; Resnina, N.; Rubanik, V.; Rubanik, V.; Volkov, A.
Abstract: The recoverable strain in shape memory bimetallic composite plates consisting of a Ti50 Ni50 alloy functional layer and a Ti49.3 Ni50.7 elastic bias layer is studied. It is shown that such plate pre-deformed by bending shows reversible shape changes on thermal cycling. Strain variations occur in the temperature ranges of the direct and reverse phase transformations with a maximum observed recoverable strain of about 0.5%. Simulation of the strain variation has been carried out based on a phenomenological model of the deformation of shape memory alloys and methods of the solid state mechanics. The calculated stress-strain and strain-temperature diagrams are presented. Dependences of the recoverable strain on the relative thickness of the functional alloy and on the residual strain caused by the preliminary deformation have been determined experimentally and by the simulation. There is a good agreement between the experimental data and the calculation results.